Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1038/nature01660
|View full text |Cite
|
Sign up to set email alerts
|

Control of osteoblast function and regulation of bone mass

Abstract: The skeleton is an efficient 'servo' (feedback-controlled/steady-state) system that continuously integrates signals and responses which sustain its functions of delivering calcium while maintaining strength. In many individuals, bone mass homeostasis starts failing in midlife, leading to bone loss, osteoporosis and debilitating fractures. Recent advances, spearheaded by genetic information, offer the opportunity to stop or reverse this downhill course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
922
0
38

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,268 publications
(972 citation statements)
references
References 66 publications
12
922
0
38
Order By: Relevance
“…Osteoblastic differentiation was substantiated by the expression of RUNX-2, a transcription factor essential for inducing osteoblast differentiation. [13][14][15][16] Cell cycle analysis showed that differentiated cells contained a higher percentage of cells in S phase (38%) with respect to undifferentiated cells. When SBP-DPSCs differentiated into osteoblasts, they gave rise also to endotheliocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Osteoblastic differentiation was substantiated by the expression of RUNX-2, a transcription factor essential for inducing osteoblast differentiation. [13][14][15][16] Cell cycle analysis showed that differentiated cells contained a higher percentage of cells in S phase (38%) with respect to undifferentiated cells. When SBP-DPSCs differentiated into osteoblasts, they gave rise also to endotheliocytes.…”
Section: Resultsmentioning
confidence: 99%
“…If this indeed is an important factor, better results would be expected for bone in older subjects that might be more adapted to their loading history. But also in fully grown bone, other factors of biological nature like calcium homeostasis or sex hormones could be physiologically more important than a bone structure perfectly adapted to its loading regime (Beaupre et al 1990;Frost 1987;Harada and Rodan 2003;Manolagas 2000;Robling et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Remodeling occurs asynchronously at millions of sites throughout the skeleton, regulated primarily by local factors including autocrine/ paracrine mediators and mechanical stimuli. In addition, systemic factors such as parathyroid hormone and estrogen modulate remodeling activity [2]. Under physiological conditions, resorption and formation are tightly coupled, and perturbations to this balance cause bone loss in metabolic diseases such as osteoporosis and inflammatory diseases such as rheumatoid arthritis and periodontitis [3].…”
Section: Introductionmentioning
confidence: 99%